Addendum: Local Elliptic Regularity for the Dirichlet Fractional Laplacian - Biccari, Umberto; Warma, Mahamadi; Zuazua, Enrique (Advanced Nonlinear Studies, 2017)
In [1], for 1 < p < 1
CRIS-Team Scopus Importer:2021-06-15
Keywords: Dirichlet Boundary Condition; Fractional Laplacian; Local Regularity; Weak Solutions